Preparation and biological evaluation of BACE1 inhibitors: Leveraging trans-cyclopropyl moieties as ligand efficient conformational constraints. Issue 1 (1st January 2020) - Winneroski, Leonard L.; Erickson, Jon A.; Green, Steven J.; Lopez, Jose E.; Stout, Stephanie L.; Porter, Warren J.; Timm, David E.; Audia, James E.; Barberis, Mario; Beck, James P.; Boggs, Leonard N.; Borders, Anthony R.; et al.
Graphical abstract: Abstract: Inhibition of BACE1 has become an important strategy in the quest for disease modifying agents to slow the progression of Alzheimer's disease. We previously reported the fragment-based discovery of LY2811376, the first BACE1 inhibitor reported to demonstrate robust reduction of human CSF Aβ in a Phase I clinical trial. We also reported on the discovery of LY2886721, a potent BACE1 inhibitor that reached phase 2 clinical trials. Herein we describe the preparation and structure activity relationships (SAR) of a series of BACE1 inhibitors utilizing trans -cyclopropyl moieties as conformational constraints. The design, details of the stereochemically complex organic synthesis, and biological activity of these BACE1 inhibitors is described.